Modelling the Effects of Fine Particulate Matter Air Pollution and Biothermal Stress on Birth Outcomes in Australia and Ghana - Nyadanu, Sylvester Dodzi (Curtin University, 2023)
High-quality environmental epidemiological methods were employed. We found that ambient fine particulate matter air pollution (PM2.5) and biothermal stress exposures independently and jointly were associated with increased risks of birth outcomes in both high-income (Australia) and low-income (Ghana) countries. The vulnerable subpopulations and critical susceptible exposure periods of early to mid-gestational periods for PM2.5 and mid to late gestational periods for the biothermal stress were identified to inform public health interventions and further investigations.